3D geometric morphometric analysis of the distal radius insertion sites of the palmar radiocarpal ligaments indicates a relationship between wrist anatomy and unique locomotor behavior in hylobatids. Issue 4 (14th June 2022) - Casado, Aroa; Cuesta‐Torralvo, Elisabeth; Pastor, Juan Francisco; De Diego, Marina; Gómez, Mónica; Ciurana, Neus; Potau, Josep Maria
Abstract: Objectives: The objective of this study is to explore the anatomical differences in the insertion sites of the palmar radiocarpal ligaments between hylobatids and other hominoids that may be related to their different locomotor behaviors. Materials and Methods: The morphology of the insertion sites of the palmar radiocarpal ligaments was analyzed with three‐dimensional geometric morphometrics (3D GM) in the distal radial epiphysis of 44 hylobatids, 25 Pan, 31 Gorilla and 15 Pongo . Results: Relative to other hominoids, hylobatid insertion sites of the palmar radiocarpal ligaments were relatively larger and the insertion site of the short radiolunate ligament had a palmar orientation. Discussion: Larger palmar radiocarpal ligaments in hylobatids can help stabilize the wrist during the radial and ulnar displacement that occurs in ricochetal brachiation, the characteristic locomotor behavior of hylobatids, and compensate for the large traction loads on the wrist during extended‐elbow vertical climbing.